PERAN KESADARAN MUZAKKI DALAM OPTIMALISASI ZAKAT UNTUK PEMBERDAYAAN MASYARAKAT PERDESAAN - Rifatul Mahfuzah; Zulkarnain Zulkarnain; Ali Asfar (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2025)
This study examines the role of muzakki awareness in optimizing zakat as an instrument for rural community empowerment. Zakat has great potential to reduce poverty, improve welfare, and promote rural economic independence when managed productively. This research employed a descriptive qualitative approach using interviews, observations, and document analysis. The findings reveal that muzakki awareness in paying zakat is influenced by religious understanding, household economic conditions, trust in zakat management institutions, and the role of religious leaders. A high level of awareness has been proven to contribute to the increase in zakat collection, which is then utilized for rural community empowerment programs such as micro-enterprise development, education, and health services. This study highlights the importance of religious value-based outreach strategies, transparency in zakat institutions, and village government synergy in strengthening the role of zakat as an instrument of rural development